From feed to food – Understanding the impact of aflatoxins consumption by Pakistani livestock - Abeera Umar; Syeda Qanita; Naeem Zada; Sabyan Faris Honey (CABI One Health)
Abstract Despite the crucial role of livestock in Pakistan’s economy, this sector remains largely overlooked, particularly concerning animal feed quality. Substandard and contaminated feed, especially with hazardous aflatoxins, poses significant challenges. This review article aims to assess the impact of aflatoxin contamination in livestock feed on animal health, productivity and food safety with a special focus on Pakistan. Aflatoxins, toxic metabolites produced by certain fungi, are frequently found in feed due to poor storage and handling practices. Their presence not only compromises animal health but also leads to their transfer through animal derived products, such as milk, meat and eggs, posing serious public health risks. Therefore, there is an urgent need for Pakistan’s livestock and food industries to recognize the significance of the issue, and to strengthen efforts to understand, monitor and control feed contamination in order to protect public health and food supply chains. This review synthesizes findings from national and international studies, highlighting the prevalence of aflatoxins in livestock feed and their residues in food products. It also discusses the regulatory standards for aflatoxins, identifies major gaps in compliance in Pakistan, and evaluates various control strategies – ranging from pre-harvest interventions and proper storage to the use of mycotoxin binders and regular feed monitoring. The findings underscore that aflatoxin levels in many feed samples often exceed permissible limits, resulting in adverse health effects on both livestock and human health. The principal conclusion emphasizes the urgent need for implementing aflatoxin control strategies in the feed supply chain. Ensuring safe, high-quality, toxin-free feed not only can improve animal health and productivity, but it will also enhance food safety and promote the opportunities for the export of animal-based products. One Health impact statement This article explains how aflatoxins in livestock feed a matter of concern are not just for animal health but also for human health. Aflatoxins in feed also affect the production and health of animal resulting in low- and poor-quality animal products. Chronic exposures of aflatoxins may lead to death of animals. The contaminated feed consumed by the animals is metabolized in the animal’s body and the metabolites are secreted in meat, milk, eggs etc. Human beings consuming these animal-based products become exposed to aflatoxins, which are potent carcinogens, also causing liver damage and immune suppression. Additionally, they cause stunted growth in children as well. The improper storage and handling of aflatoxin contaminated feed contributes to the proliferation of Aspergillus flavus, the aflatoxin-producing fungi, especially in warm and humid climate. This reflects poor agricultural practices and degraded environment which perpetuates the cycle of contamination. Contaminated feed and animal products also have economic implications, like reduced marketability of animal products, trade restrictions on animal products and increased health care cost. By adopting a trans-disciplinary approach, interventions can target the root causes of aflatoxin contamination in livestock feed, promote sustainable agricultural practices and ensure safer food systems for animal and human beings, preserving the environmental integrity.